Seasonal cycle of phytoplankton community structure and photophysiological state in the western subarctic gyre of the North Pacific. (1st May 2014) - Fujiki, Tetsuichi; Matsumoto, Kazuhiko; Mino, Yoshihisa; Sasaoka, Kosei; Wakita, Masahide; Kawakami, Hajime; Honda, Makio C.; Watanabe, Shuichi; Saino, Toshiro
Abstract : We investigated the seasonal variability of the phytoplankton community in the western subarctic gyre (WSG) of the northwestern North Pacific with respect to structure (abundance, size, and taxonomic composition) and photophysiological state from 2006 to 2012 by using the chemotaxonomy program CHEMTAX, microscopy, and fast‐repetition‐rate fluorometry. Chlorophyll a standing stock (∫Chl a ) varied seasonally from 20 to 52 mg m −2 and increased frequently to > 40 mg m −2 in June and July. Diatoms (20–35%) and prymnesiophytes (13–23%) comprised major portions of the ∫Chl a during the bloom period. Diatoms decreased to < 23% during the postbloom period, and prymnesiophytes became the most abundant group (24–35%). Mean Fv : Fm ratios (potential photochemical efficiency of photosystem II) in the mixed layer were relatively high (0.41–0.47) in winter and early spring, decreased rapidly to 0.32–0.39 concomitant with bloom development, and remained at low levels in the summer and autumn, although macronutrients [NO − 3, PO 3− 4, and Si(OH)4 ] in the mixed layer were not depleted at any time. In June 2012, onboard‐ship iron (Fe)‐enrichment experiments stimulated increases of Chl a concentrations (from 0.64 to 7.15 mg m −3 ) and Fv : Fm (from 0.33 to 0.44). Seasonal variability of the phytoplankton community in the WSG is controlled mainly by Fe, with light and temperature limitation occurring in winter and early spring. Our study also suggests that the magnitude and duration of blooms in the WSG are strongly affected by Fe availability.